Status Ca, Mg dan Zn pada Kambing Peranakan Etawah Muda yang Diberi Ransum Bentuk Mash dengan Pakan Sumber Serat Berbeda - T Toharmat; N Hotimah; E Nursasih; R Nazilah; T Q Noerzihad; N A Sigit; Y Retnani (Faculty of Animal Science, Bogor Agricultural University, 2007)
Fibrous agricultural by-products are the component of most rations for ruminant raised intensively. Slow rate and low digestibility of the fibrous feed may limit mineral bioavailability. Present experiment aimed to clarify the influence of fibrous feed component in ration on the status of Ca, Mg and Zn in growing goats. Twenty of female Etawah-grade goats weighing of 13.5±2.14 kg were grouped and allocated into five treatments in a randomized block design. Rations composed of 50% fibrous feed and 50% concentrate. The fibrous feed component as treatments were: RG = napier grass, JP = rice straw, KC = cacao pod, JK = mixed rice straw and coffee husk, and CP = mixed rice straw, napier grass, coffee husk and cacao pod. Rations were offered at 3% of live weight. The result showed that fibrous feed influenced Ca, Mg, and Zn intake, Ca and Mg absorption, and Ca, Mg and Zn plasma of growing goats. Intake, absorption and plasma Ca, Mg, and Zn had positive correlation with dry mater intake. Absorption of Ca and Zn had positive correlations with crude fiber digestibility. Supplementation of Ca, Mg and Zn was necessary when the fibrous feed was included at the level of 50% in the ration of growing goats, but the supplement level varied according to the type of the fibrous feed. Key words: fibrous feed, mineral status, Etawah goat